Triumph and Trauma: Commemorating the Conquest of Izmir in State and (Trans)Local Narrative - Janson, Torsten (MEMORY STUDIES ASSOCIATION 7th ANNUAL CONFERENCE, Newcastle, United Kingdom, 2023-07-03 - 2023-07-07, 2023)
On October 29 2023, Turkey celebrates the centenary of the Republic. We may anticipate this to be an equally spectacular and politicized event: a purported celebration of national unity, which in essence will reproduce and re-affirm distinct political wedges. Carefully choreographed national celebration has a long history in Turkey. And historiography has been its narrative bedrock, highlighting the “defining moments” of the nation along a narrative sequence of victimhood, heroism, and ultimate national triumph. The birth of the Republic is represented as a redemptive cataclysm, forging the “Turkish Nation” from idealised notions of culture, territory, language, religion, economic prosperity, and military glory. National memory tends to be solipsistic. The emergence of the Republic is represented as forward-looking, as both the promise and fulfilment of the present nation, itself on the path towards glorious future. Historical acumen is of little concern. To the contrary, a master narrative of unity and homogeneity glosses over historical complexity, domestic diversity, and political dissent, not to mention humanitarian atrocities. National celebration hence signifies amnesia as much as memory; it orchestrates silence and omission as much as pomp and circumstance. The Republic remembers its own conception. Full stop – and full circle. Idealised notions notwithstanding, Turkey (past and present) comprises complex cleavages. And the past decades have witnessed deepening polarisations: between religiously oriented and secularist political camps; between state interests and ethno-linguistic and religious minorities; between centrist bureaucracy and contesting civil society. Such cleavages, in turn, are interconnected with contesting memories – and memoryscapes. Hence the contemporary construction and contest of memory carries acute political significance. And this invites us to explore the memory of the Republic as guided by multiple voices, multiple experiences, multiple spaces, and multiple modalities of memory. It invites us to probe of the ambiguities of Turkish memory politics: • Empirically: what is the dynamic of state orchestrations of the past vis-à-vis (counter)narratives expressive of regional, local, familial, and personal memory? • Theoretically: how can we analytically frame contemporary memory debates, in a context defined by ideological polarisations – yet largely shared historiographical constructs. A context also defined by rampant political populism; of aggravating authoritarianism; and of intensifying translocal connectivity.